DBT therapeutic activity ideas for working with teens : skills and exercises for working with clients with borderline personality disorder, depression, anxiety, and other emotional sensitivities - Lozier, Carol Whitcomb, 1956- (Jessica Kingsley Publishers, 2018)
Helping teens manage emotions and develop relationships, this fun and engaging activity book tracks progress using DBT techniques. It is a concise and easy-to-read resource that presents an overview of the four skill modules of DBT: mindfulness, distress tolerance, emotion regulation, and interpersonal effectiveness. The skills used in these modules can be logged and monitored through the tick lists and diary cards provided, and help to regulate strong emotional responses which can lead to impulsivity, unstable relationships, low self-image, and reactive emotions. These practical tools and ideas are reproducible, and will be invaluable for anyone working with teens--back cover.